An historical study of the ministry of federal territories building in Putrajaya within the perspective of the discourse on the national architectural identity of administrative architecture - Mohd Rasdi, Mohd Tajuddin; Kanesh, Kavin; Utaberta, Nangkula; Asif, Nayeem (Institute of Physics Publishing, 2020)
With the establishment of a new administrative center in Putrajaya, an opportunity to address and to reaffirm a national architectural identity was presented. This research attempts to document and evaluate the design direction of administrative buildings in Putrajaya in response to the issue of establishing a national architectural identity. It will attempt to analyze the various inputs towards achieving the desired image, from the political, socio cultural as well as economic context. Additionally, it is crucial to understand the architectural identity thoughts and standpoint of the architect that was in charge of the design and implementation of the selected administrative building. This research uses a historical architectural interpretative methodology to analyze the building in place and aided with literature reviews, interviews with the relevant persons involved as well as on site direct observation and analysis of the building involved. The data obtained and presented reveals the thoughts that were the basis of forming the national architecture identity to an extent. The architect’s position in relation to achieving the design-brief but at the same time, utilizing his or her reflection and background formation. The research discovers that the architect’s design principles were to emphasize the local and Islamic characteristics to highlight the role of Islam within the new administrative center of Malaysia. The resulting outcome of this research will provide an understanding on how to critically engage in addressing architectural issues that form a national architecture identity.